An investigation of genome-wide promoter region cytosine-phosphate-guanine (CpG) Island methylation profiles in patients with chronic hepatitis B virus infection - Kgatle, Mankgopo Magdeline (Division of Human Genetics, 2014)
Includes bibliographical references.